Occupational asthma and occupational rhinitis: the united airways disease model revisited - Ameille, Jacques (BMJ Group, 2013)
OBJECTIVES: Whereas accumulating evidence indicates close associations between rhinitis and asthma, little is known about the relationships between occupational rhinitis (OR) and occupational asthma (OA). This study analyses the prevalence of OR associated with OA, globally and according to the various causal agents, and investigates the temporal relationships between these two conditions. METHODS: Data on incident cases of OA (2008–2010) were collected through the French national occupational disease surveillance and prevention network, using a standardized form including information on occupation, causal agents, presence of OR, and respective dates of occurrence of rhinitis and asthma. RESULTS: Among the 596 reported OA cases with latency period, 555 could be attributed to identified agents: high molecular weight (HMW) agents (n=174); low molecular weight (LMW) agents (n=381). Overall, OR was associated with OA in 324 (58.4%) cases. The frequency of association was significantly higher for HMW agents than for LMW agents (72.2% vs 51.5%, p<0.001). OR occurred before OA significantly more frequently for HMW agents than for LMW agents (p<0.01). CONCLUSIONS: These results show that OR is frequently associated with OA, especially when HMW agents are involved. They are consistent with the hypothesis that OR, in conjunction with OA, is more likely to be caused by sensitizers that cause disease via IgE-mediated mechanisms and suggest that symptoms of OR should be taken into account in the medical surveillance of workers exposed to HMW agents.